Cause and Treatment of Severe Cutaneous Adverse Drug Reactions at RSUP Dr. Sardjito Yogyakarta - Fatkhiya, Musa Fitri; Aina Urfiyya, Qarry Aina (Science and Community Pharmacy Journal, 2022)
SCARs is an unexpected reaction from the use of a drug which is a severe skin disorder such as SJS, TEN and DRESS. Although the incidence is low, SCAR is associated with high mortality, so needed data to show the drug that causes the biggest cause of SCAR and the treatment. The study was conducted in a retrospective descriptive with total sampling data collection techniques on the medical records of patients with a diagnosis of SJS, TEN and DRESS at RSUP Dr. Sardjito Yogyakarta from 2015 to 2019. There were 78 patients diagnosed with SCARs and 48 patients met the inclusion criteria. 23 patients diagnosed with SJS, 6 patients diagnosed with TEN and 19 patients diagnosed with DRESS. The main causative drugs in patients with SJS, TEN and DRESS were Antibiotics (50%), Analgesics (26%), Antiepileptic drugs (6%), Antidepressants, Aantifungals, Antihypertensives, Antivirals was 1% for each group and other drugs (8%). The Antibiotics that most often cause SCARs are Cephalosporins, Ceftriaxone and Cefixim. While the main therapy for SCARs, be it SJS, TEN or DRESS, is the use of systemic corticosteroids and supportive intravenous fluid therapy